The THE USE OF ENGLISH FANTASY MOVIE CLIPS TO IMPROVE STUDENTS’ LISTENING SKILLS AT SMPN 2 MAPPAKASUNGGU - Syam, Nurul Aulya; Baso, Farisha Andi; Natsir, Ratu Yulianti (FKIP Unismuh Makassar, 2023)
The aim of this research was to make sure whether the use of English fantasy movie clips was able to improve students’ listening skills at SMPN 2 Mappakasunggu. This research was conducted using the quantitative method with a pre-experimental design with one group of pre-test and post-test. This research population consisted of ninth-grade students at SMPN 2 Mappakasunggu, and the research sample was IX-A class, which consisted of 24 students, selected by purposive sampling technique. The data from this research were collected through the provision of pre-test and post-test material used as a comparison to find out how to improve students' listening skills before and after using English fantasy movie clips as learning media. The results of this research showed that the use of English fantasy movie clips as a learning medium was able to improve students' listening skills and increase their knowledge of vocabulary, especially verb.. This was indicated by an increase in student scores, where the average student pre-test score was 61.07 and the average student post-test score was 82.18, indicating an increase of 34.5% in this research. Furthermore, the results of the data analysis show that the t-test value (6.59) was higher than the t-table value (2.807) and the outcome of the hypothesis test indicated that (H₁) was accepted and (H₀) was rejected. Based on these findings, it can be interpreted that there are significant differences in students' listening skills before and after they use English fantasy movie clips as a medium for the learning process.